The DETERMINAN NILAI PERUSAHAAN DAN PERAN PEMEDIASI STRUKTUR MODAL DI LIMA NEGARA ASEAN - Muhammad Zacky; Nurmala Ahmar; JMV Mulyadi (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2018)
The purpose of this study is to determine the determinants of firm value and the role of mediating capital structure in five ASEAN countries. Objects in this study were companies listed on the stock exchanges in Indonesia, Cambodia, Laos, Malaysia and the Philippines in 2014 - 2016. The sampling method used in this study was purposive sampling, resulting in 97 companies. The collected data were analyzed using descriptive and statistical analysis techniques, using the WarpPLS 6.0 and SPSS version 24 programs. The results showed that the profitability and growth opportunity variables affected the capital structure, while the dividend policy had no effect. Variable profitability, dividend policy and capital structure affect the value of the company, while growth opportunity does not affect. Profitability of firm value through capital structure results in partial mediation, growth opportunity on firm value through capital structure produces full mediation and dividend policy on firm value through capital structure produces no mediation. It is recommended for further research to increase the number of respondents, the sample of the company under study, and the indicators of each variable